Asymptomatic children with multiple endocrine neoplasia type 1 mutations may harbor nonfunctioning pancreatic neuroendocrine tumors. - Newey, P; Jeyabalan, J; Walls, G; Christie, P; Gleeson, F; Gould, S; Johnson, P; Phillips, R; Ryan, F; Shine, B; Bowl, MR; Thakker, R (2009)
CONTEXT: Multiple endocrine neoplasia type 1 (MEN1) is characterized by the occurrence of parathyroid, pituitary, and pancreatic tumors. MEN1, an autosomal dominant disorder, has a high degree of penetrance, such that more than 95% of patients develop clinical manifestations by the fifth decade, although this is lower at approximately 50% by age 20 yr. However, the lower penetrance in the younger group, which is based on detecting hormone-secreting tumors, may be an underestimate because patients may have nonfunctioning tumors and be asymptomatic. OBJECTIVE: The aim of the study was to evaluate the occurrence of nonfunctioning pancreatic neuroendocrine tumors in asymptomatic children with MEN1. PATIENTS: Twelve asymptomatic Northern European children, aged 6 to 16 yr, who were known to have MEN1 mutations were studied. RESULTS: Two asymptomatic children, who were aged 12 and 14 yr, had normal plasma fasting gastrointestinal hormones and were found to have nonfunctioning pancreatic neuroendocrine tumors that were more than 2 cm in size. Surgery and immunostaining revealed that the tumors did not have significant expression of gastrointestinal hormones but did contain chromogranin A and synaptophysin, features consistent with those of nonfunctioning pancreatic neuroendocrine tumors. The tumors had a loss of menin expression. The 14 yr old also had primary hyperparathyroidism and a microprolactinoma, and the 12 yr old had a nonfunctioning pituitary microadenoma. Three other children had primary hyperparathyroidism and a microprolactinoma. CONCLUSION: Nonfunctioning pancreatic neuroendocrine tumors may occur in asymptomatic children with MEN1 mutations, and screening for such enteropancreatic tumors in MEN1 children should be considered earlier than the age of 20 yr, as is currently recommended by the international guidelines.